Livelihood transformation in Pangi Village: Navigating the socio-economic dynamics of the shift from agriculture to gold mining - Sahrain Bumulo; Rauf A. Hatu; Dare Ojo Omonijo; Dewinta Rizky R. Hatu; Ridwan Ibrahim; Sainudin Latare; Rudy Harold; Marsela Madi (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2026)
This study examines the socio-economic transformation in Pangi Village, Gorontalo, Indonesia, marked by a significant shift from agriculture to artisanal and small-scale gold mining (ASGM), driven primarily by declining agricultural productivity and increasing economic uncertainty. This study adopts a qualitative research approach to examine the socio-economic and environmental implications of the livelihood transition. Data were collected through in-depth interviews with farmers, miners, village officials, and community leaders, complemented by field observations in both agricultural and mining areas. The data were analyzed thematically to capture community perceptions, lived experiences, and local responses to the changing rural economic landscape. The findings indicate that while ASGM offers higher income potential than agriculture, it also generates significant social and environmental consequences. Social relations within the village have become increasingly fragmented, particularly between households engaged in mining activities and those remaining in the agricultural sector. In addition, mining activities have contributed to land degradation and water pollution, further threatening the sustainability of agricultural practices. Government initiatives aimed at protecting agricultural land and revitalizing the farming sector have not yet achieved optimal outcomes, as they have failed to provide rapid and tangible improvements in farmers’ welfare. As a result, despite awareness of the risks associated with mining, many residents continue to abandon agriculture in favour of ASGM. The findings highlight that the livelihood transition is driven by persistent economic pressures and limited agricultural viability, while simultaneously generating social fragmentation and environmental degradation. This study contributes to a deeper understanding of rural livelihood transformations by revealing how economic vulnerability shapes community responses and policy outcomes. These results underscore the need for integrated policies that strengthen agricultural competitiveness, enhance farmer empowerment, and balance economic development with environmental sustainability to ensure long-term rural welfare.